Kajian Konsep Arsitektur Ekologis pada Terminal Intermoda Joyoboyo (TIJ) Surabaya - Fahmi Amrullah; Winarsih, Sri Suryani Yuprapti (Politeknik Negeri FakFak, 2025)
. Joyoboyo Intermodal Terminal (TIJ) Surabaya is one of the transportation infrastructures that integrates various modes of transportation, including buses and city transportation. In the context of sustainable urban development, ecological architecture is essential for creating public spaces that are environmentally friendly, efficient, and sustainable. This research aims to examine the concept of ecological architecture applied to TIJ, focusing on design elements that support energy efficiency, the use of environmentally friendly materials, and optimal management of natural resources. In this analysis, Heinz Frick's principles of ecological architecture are also applied, which are the reference in designing buildings that harmonize nature and technology. The research method used is qualitative analysis with a case study approach, where field observation, interviews, and architectural documentation are the main tools in collecting data.